Perspective Prof. Ts. Dr. Haji Mohamad Kamal Haji Harun - UiTM, Korporat UiTM (Corporate Communications Department, 2019)
Perspective Prof. Ts. Dr. Haji Mohamad Kamal Haji Harun, Deputy Vice-Chancellor (Academic and International) shares insight into UiTM's academic landscape.